(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This essay shares experiences related to graduate student well-being in the transition from face-to-face to virtual learning during the COVID-19 pandemic. The unexpected and rapid changes due to the preventive measures taken created challenges for both educators and students in the middle of the Spring 2020 semester. In navigating these challenges, we sought ways to tend to students’ well-being without sacrificing quality and discovered students needed a safe space to share their experiences and feelings which helped them connect with each other at a deeper level and develop a sense of community.